2018
DOI: 10.1016/j.jinf.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of Escherichia coli bacteraemia isolates originating from urinary tract foci contain more virulence-associated genes than those from non-urinary foci and neutropaenic hosts

Abstract: ObjectivesEscherichia coli is the leading cause of bacteraemia. In an era of emerging multi-drug-resistant strains, development of effective preventative strategies will be informed by knowledge of strain diversity associated with specific infective syndromes/patient groups. We hypothesised that the number of virulence factor (VF) genes amongst bacteraemia isolates from neutropaenic patients would be lower than isolates from immunocompetent patients.MethodsImmunocompetent and neutropaenic adults with E. coli b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
8
2
Order By: Relevance
“…Despite studies reporting various VAGs linked to pyelonephritis and sepsis [15, 114, 115], we found no single gene nor plasmid replicon strongly associated with a particular pathology (correlation heat map in Data S5), nor was there a significant difference between the number of VAGs present and uro-clinical syndrome (). The discrepancy with the literature may have arisen due to sampling based on trimethoprim resistance and/or the relatively small sample size, limiting statistical power.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Despite studies reporting various VAGs linked to pyelonephritis and sepsis [15, 114, 115], we found no single gene nor plasmid replicon strongly associated with a particular pathology (correlation heat map in Data S5), nor was there a significant difference between the number of VAGs present and uro-clinical syndrome (). The discrepancy with the literature may have arisen due to sampling based on trimethoprim resistance and/or the relatively small sample size, limiting statistical power.…”
Section: Resultscontrasting
confidence: 73%
“…Despite studies reporting various VAGs linked to pyelonephritis and sepsis [15,114,115], we found no single gene nor plasmid replicon strongly associated with a particular pathology (correlation heat map in Data S5), nor was there a significant difference between the number of VAGs present and uro-clinical syndrome (Fig. 7a).…”
Section: Class 1 and 2 Integronscontrasting
confidence: 60%
“…The hlyA gene was detected in 32.99% of the E. coli isolates. In Iran, Malekzadegan and Khashei22 reported that 28.6% of the E. coli strains were positive for hlyA , whereas Dale et al33 found that 26% of E. coli strains in the UK carried hlyA , and Bozcal et al34 identified this gene in 15.4% of E. coli strains in Turkey. The percentage of E. coli harboring hlyA in our study was higher than detected in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Abricate (https://github.com/tseemann/abricate) v0.8.13 was used for (i) mass screening of contigs for (acquired) antimicrobial resistance genes using ResFinder 3.1.0 (download 24 January 2019), and (ii) to determine presence of VG by BLAST against the VFDB database (http://www.mgc.ac.cn/VFs) (download 8 February 2019) [16,17]. We searched for 49 putative VG that were previously described as extra-intestinal pathogenic E. coli (ExPEC)-associated VG [18][19][20][21][22]. If any of the predefined VG were not included in VFDB, BLAST against the eco-li_VF_collection database was performed (date 8 February 2019) [23].…”
Section: Antimicrobial Resistance Genes and Virulence Genesmentioning
confidence: 99%